Teachers' Strategies in Developing Students' Character at SDIT Alif Cendekia Gowa - Indar, Indar; Mahmud, Moh. Natsir; U, M. Shabir (Jurnal Mercusuar, 2021)
The purpose of this research is to analyze the strategies of teachers in developing the character of students at SDIT Alif Cendekia Gowa. The type of research used is qualitative research with a phenomenological approach. The data collection methods used were interviews, observation, and documentation. The data processing and analysis techniques were conducted through four stages, namely data condensation, data presentation, and drawing conclusions. The results of the study show that the teachers' strategies in developing the character of students at SDIT Alif Cendekia Gowa are by providing examples, habits, guidance, motivation, reprimands, and rewards and punishments. The implications of this study are: 1) All ustaz/ustazah at SDIT Alif Cendekia Gowa are expected to be more effective in shaping the character of students and should always motivate students in and outside of class, so that the learning objectives can be achieved well. 2) Always provide good examples to students so that they can be emulated by all students to create good character or personality by imitating every action of the ustaz/ustazah. 3) Provide special attention to students who do not understand the learning material presented with several methods or approaches in learning such as individual approaches given to students. 4) Parental support in the form of active participation in every school activity should be in line with what is done at home, especially the examples and supervision in the family and community environment.